Научная деятельность М.Ф. Болтенко в Одесском археологическом музеес 1921 г. по 1934 г. - Колесниченко, А.Н. (Материалы по археологии Северного Причерноморья, 2015)
Mikhail Fedorovich Boltenko (1888-1959) is a famous archaeologist, historian, philologist, who worked in Odessa Archaeological Museum. In 1920 he entered museum as scientific keeper. During 1930–1933 M.F. Boltenko was a director of Museum. In 1920-30-ies he carried out archaeological excavations on the Usatove settlement, on the Berezan island and in Olbia. His research became precious contribution to the development of archaeology and were acknowledged also abroad. Manuscripts of Boltenko is kept in Odessa Archaeological Museum’s archive. They are per se an important source of information for modern archaeologists. Their publication is actual and scientifically important.